Comparative studies on catalytic and non-catalytic co-gasification of rubber seed shell and high density polyethylene mixtures - Chin, B.L.F. (Elsevier Ltd, 2014)
The thermal degradation behavior of rubber seed shell, high density polyethylene waste, and the binary mixtures of high density polyethylene and rubber seed shell (0.2:0.8 weight ratio) are compared in pyrolysis, gasification, and catalytic gasification process at different heating rate of 10, 20, 30 and 50 K min-1 in temperature range of 323-1173 K using thermogravimetric analysis equipment. It is observed that there are one, two, and three stages of decomposition occurring in high density polyethylene, rubber seed shell, and the binary mixtures respectively regardless of the process involved. The activation energies, EA and pre-exponential factor, A are generated using one step integral method based on first order rate of reaction. Besides that, the synergistic effect on the binary mixtures is also investigated for the three different processes involved. It is found that the EA and A values for the binary mixtures are lower than the pure high density polyethylene but comparable to pure rubber seed shell regardless of the processes involved. In addition, it is also observed that the EA and A values are slightly lower when catalyst is added in the binary mixtures compared to the absence of catalyst in the gasification process. Â© 2014 Elsevier Ltd. All rights reserved.